Revision of the genus Rhytidaspis Redtenbacher, 1891 including the description of a new genus Haudrhytidaspis gen. nov. (Orthoptera: Tettigoniidae: Conocephalinae) - Ingrisch, Sigfrid (Zootaxa, 2019)
The genus Rhytidaspis Redtenbacher, 1891 is revised. The species R. fusca (Karny, 1911) is removed from the genus and combined with Haudrhytidaspis gen. nov. as type species, leaving only the type species R. picta Redtenbacher, 1891 in Rhytidaspis. The shapes of the male cerci and the complex structure of the male titillators in Rhytidaspis allows to differentiate between seven species and two subspecies of which six species and two subspecies are new to science: R. arfak sp. n., R. camela sp. n., R. genyem sp. n., R. nigropunctata sp. n., R. ornata sp. n., R. variata sp. n., R. variata brevis ssp. n., R. variata meja ssp. n.. A dichotomic key to species and a distribution map are provided. All records of Rhytidaspis known so far are from western New Guinea: Papua and Papua Barat (Indonesia) including Waigeo Island. Haudrhytidaspis fusca (Karny, 1911) had been described from New Guinea without precision.